EpCAM-Mediated Cellular Plasticity Promotes Radiation Resistance and Metastasis in Breast Cancer - Mal, Arijit; Bukhari, Amirali B.; Singh, Ram K.; Kapoor, Aastha; Barai, Amlan; Deshpande, Ishan; Wadasadawala, Tabassum; Ray, Pritha; Sen, Shamik; De, Abhijit (Frontiers in Cell and Developmental Biology, 2021)
A substantial number of breast cancer (BC) patients undergoing radiation therapy (RT) develop local recurrence over time. During RT therapy, cells can gradually acquire resistance implying adaptive radioresistance. Here we probe the mechanisms underlying this acquired resistance by first establishing radioresistant lines using ZR-75-1 and MCF-7 BC cells through repeated exposure to sub-lethal fractionated dose of 2Gy up to 15 fractions. Radioresistance was found to be associated with increased cancer stem cells (CSCs) and elevated EpCAM expression in the cell population. A retrospective analysis of the TCGA dataset indicated a positive correlation of high EpCAM expression with poor response to RT. Intriguingly, elevated EpCAM expression in the radioresistant CSCs raises the bigger question of how this biomarker expression contributes during radiation treatment in BC. Thereafter, we establish EpCAM overexpressing ZR-75-1 cells (ZR-75-1EpCAM), which conferred radioresistance, increased stemness through enhanced AKT activation and induced a hybrid epithelial/mesenchymal phenotype with enhanced contractility and invasiveness. In line with these observations, orthotopic implantation of ZR-75-1EpCAM cells exhibited faster growth, lesser sensitivity to radiation therapy, and increased lung metastasis than baseline ZR-75-1 cells in mice. In summary, this study shows that similar to radioresistant BC cells, EpCAM overexpressing cells show a high degree of plasticity and heterogeneity which ultimately induces radioresistant and metastatic behavior of cancer cells, thus aggravating the disease condition.